SOCIO-ECONOMIC IMPACTS OF CIRCULAR BUSINESS MODELS: A COMPREHENSIVE LITERATURE REVIEW - Loso Judijanto; Silvia Ekasari (INJOSEDU: International Journal of Social and Education, 2025)
This research aims to explore the social and economic impacts of implementing circular business models through a comprehensive literature review. Circular business models offer solutions to address sustainability challenges, by promoting the principles of recycling, reuse and waste reduction to optimise resources. The review shows that this approach contributes to economic sustainability by creating efficiencies in the value chain, while introducing opportunities for technological innovations that support better resource management. Moreover, from a social perspective, circular business models can create quality jobs, promote community empowerment, and reduce social inequality. However, the implementation of this model faces a number of challenges, such as organisational resistance, large investment needs, and complex policy adaptations. Thus, while the circular business model has great potential for positive impact, it requires cross-sector collaboration for successful implementation.